Analisis Pengaruh Game Online Mobile Legends Terhadap Minat Belajar Siswa Kelas V Di SDN Cibunigeulis 1 - Ajis, Helmi; Zahrah, Riza Fatimah; Mahendra, Hatma Heris (CV. Generasi Insan Rafflesia, 2024)
This study aims to determine the analysis of the influence of the online game mobile legends on the learning interest of fifth grade students at SDN Cibunigeulis 1. Problems in the study The low learning interest of fifth grade students at SDN Cibunigeulis 1 which is influenced by the online game mobilegends. The method used in this study is descriptive qualitative. Data collection techniques in this study include observation, interviews and documentation. The results of the study showed that the habit of playing online games, especially Mobile Legends, among fifth grade students at SDN Cibunigeulis was influenced by several important factors that had a significant impact on their academic and social lives. This study also revealed that the motivation behind the habit of playing games varied between students, with factors such as peer influence, competition, accessibility, and escape from stress being the main drivers.